Health promotion research in the Nordic countries - a scoping review of PhD dissertations 2008-2018. (20th October 2021) - Eriksson, C; Andersen, H M; Eriksson, A; Johannessen, A; Simonsen, N; Thualagant, N; Torp, S; Haglund, B J A
Abstract: Background: The Nordic countries are welfare states that also have been claimed to be in the forefront in developing health promotion, in relation to theory, research, policy and practice. This scoping review was performed by members of the Nordic Health Promotion Research Network with the objectives to collect and identify the scope and theoretical basis of doctoral (PhD) dissertations on health promotion in a Nordic context. Methods: Searches for dissertations, published 2008-2018, were performed in several databases in Denmark, Finland, Iceland, Norway, and Sweden. Those labelled "health promotion" present in titles, abstract or key words were included in the scoping review. Data was extracted based on a common template including title, aims, university, individual-national level, setting, type of study and collaboration. Results: The search strategy had to be modified to include manual searches at university sites as no national data base was available. In total, 353 health promotion dissertations had been published at 41 different universities. Most dissertations were Swedish (193), while 56 came from Denmark, 53 from Norway and 51 from Finland, but non from Iceland. The main content was lifestyle (28%), mental or psychosocial health (14%), critical health promotion (8%), empowerment (7%) or refugee and immigrants (5%). The most common approach was settings (31%), including health care setting (14%), followed by societal (28%) and individual (28%) approaches. Mixed methods approach was most common research method (45%) followed by quantitative (32%) and qualitative methods (23%). Large country variations were seen in the health promotion. Conclusions: Health promotion research in the Nordic countries can be characterised by focusing on lifestyle, settings approach, and primarily using a mixed methods approach. However, there are large variations between different health promotion PhDs, also including dissertations on critical health promotion and empowerment. Key messages: Analysis of PhD dissertations can contribute to more comprehensive insight in disciplinary development. The research training will have implications for the future public health workforce. The Nordic collaboration enabled an extensive scoping review of PhD dissertations on health promotion research in the Nordic countries and shows what has characterized the field of research.